2017
DOI: 10.1111/ped.13304
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐prefecture disparity in under‐5 mortality: 115 year trend in Japan

Abstract: The disparities in child health appear to be widening, and may serve as a warning to today's society that increasing socioeconomic gradients may lead to rising health inequity among children. Further investigations into the causes, mechanisms, and possible interventions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Previous studies have shown that natural disasters can cause a temporary increase in mortality, especially among the most vulnerable 35 . While we could not detect such a spike in deaths in our study, we cannot rule out the possibility that such an influence was not evident because of the small sample size.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have shown that natural disasters can cause a temporary increase in mortality, especially among the most vulnerable 35 . While we could not detect such a spike in deaths in our study, we cannot rule out the possibility that such an influence was not evident because of the small sample size.…”
Section: Discussioncontrasting
confidence: 82%
“…4 However, these risks are not necessarily homogeneous across the regions of Japan. For example, Nagata et al (2017) recently reported that inter-prefecture inequality in child mortality had increased since the 2000s. 5 This increase in inequality in regional child mortality may be linked to changes in some of the social determinants of child mortality observed across highincome countries that include relative poverty, income inequality and social policies, such as workplace maternal leave policies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nagata et al (2017) recently reported that inter-prefecture inequality in child mortality had increased since the 2000s. 5 This increase in inequality in regional child mortality may be linked to changes in some of the social determinants of child mortality observed across highincome countries that include relative poverty, income inequality and social policies, such as workplace maternal leave policies. [6][7][8] As the relative poverty rate for children in Japan increased by 1.5 times from 1985 to 2012, it is possible that an expansion in social and economic differences might also be affecting the IMR and increasing regional inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities are known to exist in the rates of both infant and adult mortality among prefectures in Japan [49,50], and understanding and correcting the differences in perinatal outcomes among regions might contribute to improving these disparities in the future. There are some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%